Mass spectrometry measurements of mercury isotope ratios support geochemical sourcing of archaeological cinnabar in the Andean region - Michelle Young; Colin Cooke; Richard Burger; Emily Kaplan; Gabriel Prieto; Jacob Bongers; Jordan Dalton; Fathima Usama; Shengliu Yuan; Holger Hintelmann (PLoS ONE, 2025)
Geochemical methods can identify the long-distance exchange of resources in the archaeological record. Cinnabar is a mineral with a limited number of geological sources; however, methods for determining the geological origin of cinnabar are constricted by the limited availability of comparative geological source materials. This study applies a multi-method approach to compare isotopic ratios of mercury and sulfur in archaeological specimens of cinnabar from museum collections and scientifically excavated materials from the Andes region of South America. We demonstrate that the δ202Hg to Δ199Hg relationship, assessed through Multicollector Inductively Coupled Plasma Mass Spectrometry (MC-ICP-MS), falls along a predictive slope, while Isotope Ratio Mass Spectrometry (IR-MS) for sulfur (S) was not a reliable proxy for determining ore source. Furthermore, Hg isotope ratios from similar sites and contexts tended to cluster, suggesting that most sites exploited cinnabar from the same ore source. Statistical analyses support the idea that the Huancavelica deposit served as the primary source of cinnabar pigment for pre-Hispanic societies, while also revealing some intriguing divergences that suggest alternate sources were exploited during certain periods on the North and South Coasts of Peru. These results demonstrate that MC-ICP-MS analyses of mercury can be used to geochemically trace cinnabar ore in the Andes and beyond.